2015
DOI: 10.4103/0970-4388.160366
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of molar incisor hypomineralization in children aged 11-16 years of a city in Karnataka, Davangere

Abstract: The prevalence of MIH in the permanent dentition of south Indian children was 8.9%. There is a need for a proper planned preventive and restorative program with regard to the increasing prevalence of MIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 2 publications
4
14
1
4
Order By: Relevance
“…This is in accordance with other studies [10,16]. Kirthiga et al in their study found that the mean DMFT value in respondents affected with MIH was 3.2, which was significantly higher than the mean DMFT value of controls (0.8) [17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in accordance with other studies [10,16]. Kirthiga et al in their study found that the mean DMFT value in respondents affected with MIH was 3.2, which was significantly higher than the mean DMFT value of controls (0.8) [17].…”
Section: Discussionsupporting
confidence: 91%
“…Ovakav rezultat je u skladu s nalazima drugih istraživanja [10,16]. Istraživanje Kirthige i saradnika u Indiji, 2015. godine, ustanovilo je KIP 3,2 kod dece sa MIH-om, što je znatno više od KIP vrednosti u kontrolnoj grupi (0,8) [17].…”
Section: Rezultatiunclassified
“…In spite of the fact that the variations witnessed in regards the susceptibility of upper and lower permanent molars to MIH has been highlighted in the current study, with a greater degree of prevalence identified in the case of upper permanent molars than lower permanent molars, this has not been proven with certainty. Nonetheless, other studies display similar findings 22,23,37 . Other works have highlighted that there is a greater prevalence witnessed across mandibular molars in their sample populations 29,33,36 ,with a number of elements potentially influencing this finding, including the sitting position of the individual whilst being examined, lighting conditions, and the criteria adopted, to name a few.…”
Section: Discussionsupporting
confidence: 70%
“…Presence of hypo-mineralization and caries in the same tooth might affect the proper diagnosis of enamel breakdown whether it is actually due to caries or hypo-mineralization or a combination of both. Similar to other studies (Cho et al, 2008;Kirthiga et al, 2015), in the present study, PFM with caries, post-eruption enamel breakdown or restoration was recorded as MIH if demarcated enamel opacities remained at the borders or on the other surfaces. This might explain the large number of PFMs with post-eruptive enamel break down observed in the present study.…”
Section: Discussion:-supporting
confidence: 62%